PEMBERDAYAAN EKONOMI KREATIF MELALUI LIMBAH SAMPAH MENJADI BARANG KERAJINAN BERNILAI EKONOMI - YENIASARI RIZKIA BUDI (Institut Bisnis Muhammadiyah Bekasi, 2021)
Some people think that waste can be damaging for the environment and have no value. But it is different from those whose lives depend on the selected waste. Waste, which is considered worthless, can actually be used for economic empowerment creations. It also perhaps would help the residents who lived there, where they can use their creativity, by processing unused waste materials so that it can be useful and increase children's creativity. They can produce an item that has selling-value, and of course will be able to help the family economy. This activity is able to encourage people to make choices and sorting of waste in their homes. Garbage does not only have a bad impact, but also could make us learn to make useful and added value creations.